2014
DOI: 10.1007/s40618-013-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and sarcopenic obesity and their association with dyslipidemia in Korean elderly men: the 2008–2010 Korea National Health and Nutrition Examination Survey

Abstract: In Korean elderly men, SO was associated with an increased risk for dyslipidemia compared with sarcopenia or obesity alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 28 publications
11
77
2
6
Order By: Relevance
“…Several cross-sectional studies in Korean populations of older adults have found that sarcopenic obese individuals had the worse cardiovascular risk profile. Sarcopenic obesity (based on skeletal muscle assessed by DXA and obesity measured by either computerised tomography, DXA, BMI or WC) was associated with lower cardiorespiratory fitness, higher fasting glucose levels, a higher risk of hypertension, dyslipidaemia and insulin resistance, and up to an 8-fold increase in risk of the metabolic syndrome compared with non-sarcopenic, non-obese (48)(49)(50)(51)(52)(53)(54)(55) . Similar findings were reported in a community-dwelling sample of Taiwanese older adults; sarcopenic obesity (defined by BIA-measured muscle mass and BMI) was associated with the highest risk of metabolic syndrome (56) .…”
mentioning
confidence: 99%
“…Several cross-sectional studies in Korean populations of older adults have found that sarcopenic obese individuals had the worse cardiovascular risk profile. Sarcopenic obesity (based on skeletal muscle assessed by DXA and obesity measured by either computerised tomography, DXA, BMI or WC) was associated with lower cardiorespiratory fitness, higher fasting glucose levels, a higher risk of hypertension, dyslipidaemia and insulin resistance, and up to an 8-fold increase in risk of the metabolic syndrome compared with non-sarcopenic, non-obese (48)(49)(50)(51)(52)(53)(54)(55) . Similar findings were reported in a community-dwelling sample of Taiwanese older adults; sarcopenic obesity (defined by BIA-measured muscle mass and BMI) was associated with the highest risk of metabolic syndrome (56) .…”
mentioning
confidence: 99%
“…Janssen et al (29), in turn, in 2002 proposed a definition of sarcopenia with the skeletal mass index (SMI) by the skeletal MM divided by body mass of the subject, both in kilograms and multiplied by 100 [(MM/body mass)x100], so that individuals were considered to have a normal SMI if their SMI was greater than one SD above the sex-specific mean for young adults (aged . ASM adjusted by the body mass has been described as the most appropriate index to identify sarcopenia (5,7,15). A definition of sarcopenia was proposed by The European Working Group on Sarcopenia in Older People, in 2010, and suggests consider for diagnosing sarcopenia, not only the amount of MM but the presence of both changes, deficit of MM and low muscle function (25,30), but this criterion was not used in the studies found.…”
Section: Sarcopenic Obesity (Definition Diagnosis and Physiopathology)mentioning
confidence: 99%
“…Many explanations for SO have been proposed and evidences suggest that a vicious cycle between the accumulation of AT and the deficit of MM is responsible for keeping the development of the phenotype (22). The increase of AT, especially visceral fat, as well as the excess of free fatty acids may induce chronic inflammation by increased secretion of pro-inflammatory cytokines such as TNF-α and interleukin-6 (15,22). The inflammatory process, in turn, not only causes degradation of MM but also promotes insulin resistance (15) that contributes to the changes in the morphology, size and muscle function, leading to the onset and progression of sarcoepnia (22,32).…”
Section: Sarcopenic Obesity (Definition Diagnosis and Physiopathology)mentioning
confidence: 99%
See 2 more Smart Citations